ANALISIS KDRT DAN POLEMIK KELUARGA DALAM TINJAUAN HUKUM KELUARGA ISLAM MENURUT KACAMATA AL-QUR’AN DAN HADIST - Siregar, Samaruddin (El-Sirry: Jurnal Hukum Islam dan Sosial, 2023)
The primary mission of the Qur'an is to liberate humans from various forms of discrimination and oppression, including sexual discrimination, skin color, ethnicity, and other primordial ties, as well as acts of violence and persecution. The relationship between husband and wife is complementary. The husband is the wife's protector, and the wife is the husband's friend. In the eyes of the wife, the husband is an authoritative figure who has the power to protect her. And a wife, in her husband's eyes, is an angel who is always loyal to accompany him, and he really trusts her. How to deal with a nusyuz wife can be resolved in the way regulated in Surah An-Nisa verse 34, namely: when the wife's disobedience becomes clear, the husband has the right to advise her, after the wife's disobedience becomes visible, the husband has the right to separate from sleeping with her, if he If you are still disobedient then your husband has the right to hit him (with a blow that doesn't hurt) and the way to deal with a nuzyuz/tyrannical husband is by implementing the Shari'a as stated in Surah an-Nisa verse 128, namely by the wife sending a judge/peacemaker to resolve family problems. Between the husband and the wife.